The importance of cultural differences in international business - Marzena Adamczyk (The Central European Review of Economics and Management (CEREM), 2017)
Aim: The aim of this study is to systematize the knowledge on the characteristics and classification of cultures, which will allow national representatives to be assigned to their respective types of cultures, and to present the characteristics of selected countries in some business areas.Design / Research Method: The applied research method is the analysis of the literature in the field of cross-cultural determinants of business and the description of the findings observed and analyzed in theprocess of deductive conclusions.Conclusions / findings: The main conclusion of the research is confirming the view that cultural differences in today's global economy can significantly affect the business in an international context. In order to eliminate or actually to minimize the cultural factor of entrepreneurs, those operating on the international market should diagnose the culture of the country with which they will enter into business relationships and they should develop strategies in different markets taking into account the diagnosis made.Originality / value of the paper: The paper is a voice in the scientific discussion on the impact of cultural differences on international business; it can provide guidance and inspiration for entrepreneurs, helping them to understand the complexity of the issue, and for students interested in cultural diversity and its impact on business. The paper comprehensively connects the characteristics of national cultures with different areas of international business and shows the relationship and complexity of the issue. Such a presentation of the problem shows how important it is to know these differences for proper management of the company.Implications of the research: This paper focuses on the overall functioning of the company on the international market and discusses the cultural differences associated with the negotiation process. It may be the beginning of further research related to cross-cultural communication and management of transnational corporations and international marketing. – – Cel: Celem niniejszego opracowania jest systematyzacja wiedzy na temat charakterystyki i podziałukultur, ktoŕa pozwoli na przyporzadkowanie przedstawicieli poszczegoĺnych panśtw do odpowiednichdla nich rodzajoẃ kultur oraz przedstawienie cech charakterystycznych dla wybranych panśtw wniektoŕych obszarach biznesowych.Metodyka badan\': Zastosowana metoda badawcza to analiza literatury z zakresu miedzykulturowychuwarunkowanb́iznesu oraz opis zaobserwowanych i przeanalizowanych w procesie dedukcjiwnioskoẃ.Wnioski: Głoẃnym wnioskiem badanj́est potwierdzenie tezy, zė roźṅice kulturowe we wspoĺczesnejgospodarce sẃiatowej moga w znaczacy sposob́ wpływacńa biznes w konteksćie miedzynarodowym.W celu wyeliminowania, a raczej zminimalizowania czynnika kulturowego przedsiebiorcy działajacyna rynku miedzynarodowym powinni dokonacŕozpoznania kultury kraju, z ktoŕym beda wchodzicẃrelacje biznesowe oraz powinni opracowacśtrategie działania na roźṅych rynkach, uwzgledniajacdokonane rozpoznanie.Wartosćártykułu: Artykuł jest głosem w dyskusji naukowej na temat wpływu roźṅic kulturowych nabiznes miedzynarodowy, mozė stanowicźŕod́ło wskazoẃek i inspiracji dla przedsiebiorcoẃ,pomagajac zrozumiecźłozȯnosćźagadnienia, oraz dla studentoẃ zainteresowanych kwestiami roźṅickulturowych i ich wpływu na biznes. Artykuł w sposob́ kompleksowy łaczy charakterystyke kulturnarodowych z roźṅymi obszarami biznesu miedzynarodowego oraz pokazuje powiazania i złozȯnosćźagadnienia. Taka prezentacja problemu wskazuje, jak wazṅa jest znajomosćŕoźṅic kulturowych wodpowiednim zarzadzaniu przedsiebiorstwem.Implikacje badan\': Artykuł koncentruje sie na ogoĺnym funkcjonowaniu przedsiebiorstwa na rynkumiedzynarodowym i omawia w szczegoĺnosći roźṅice kulturowe zwiazane z procesem negocjowania.Jednoczesńie mozė bycṕoczatkiem dalszych badanźwiazanych z komunikacja miedzykulturowa,zarzadzaniem w korporacjach transnarodowych i marketingiem miedzynarodowym.
Keywords: F23; M14; Z10; 330; Culture; cultural differences; international business; intercultural communication; intercultural competence